ANALYSIS OF LETTER AL-BAQARAH VERSE 62 IN STRENGTHENING THE EMERGENCE OF SPIRITUAL SENSES AMONG RELIGIOUS PEOPLE IN INDONESIA VISITED FROM METAPHYSICS - Syarifuddin, Syarifuddin (Proceeding International Seminar of Islamic Studies, 2024)
The Indonesian nation is a pluralistic nation that has various religions, ethnicities and languages. Indonesia's ideology is Pancasila, the first principle reads,